4G By WiMAX2 and LTE-Advance - Singh, Rajinder (International Journal of Computer Sciences and Engineering, 2013)
4G refers to the fourth generation of wireless communications. Two emerging technologies Mobile WiMAX standard and Long Term Evolution (LTE) standard are being considered as candidates for the fourth generation (4G) of mobile networks. But initial versions of these two were not able to fulfill the requirement set by International Telecommunications Union. In this paper a comparison of their later versions WiMAX2 and LTE-Advance standards has been made.